(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The basis of the sustainable development of society with ever-growing scientific and technical progress is noxology as a science about the dangers of the world, since the risk of being in modern society is higher than ever. In this regard, a scientific noxospheric picture of the world is being formed as an integrative knowledge system, which should be the basis for the formation of a new, noxological worldview, in which security is the main value norm of risk-oriented thinking. The article is aimed at the theoretical substantiation of the necessity of developing a risk-balanced style of professional activity among university students on the basis of risk-thinking as an objective property of the personality. The article also reveals the authors’ concept of the noxological consciousness and explains the term of a risk-balanced style of professional activity. The definition, structure and main constituent elements of this personal phenomenon are given. It is determined that noxological style of professional activity includes such components as risk-thinking, self-regulation, intellectual features and capabilities, “labor model”, individual biological rhythms, will, as well as habits and special techniques of activity. Various characteristics of risks in the professional activity of a specialist are considered. Based on the analysis of scientific and pedagogical literature on the problem and the method of observation, the modeling of the pedagogical system of training a specialist with a risk-balanced style of professional activity is presented, the effectiveness of which is confirmed by the formative experiment.